Metyrapone single administration, as a possible predictive tool of its dosage and timing in Cushing’s syndrome - Tsujimoto, Yasutaka; Yamamoto, Naoki; Bando, Hironori; Yamamoto, Masaaki; Ohmachi, Yuka; Motomura, Yuma; Oi-Yo, Yuka; Sasaki, Yuriko; Suzuki, Masaki; Urai, Shin; Takahashi, Michiko; Iguchi, Genzo; et al. (Frontiers in Endocrinology, 2024)
Metyrapone is commonly used in the initial management of Cushing’s syndrome to reduce hypercortisolemia, but its optimal dosage and timing can vary significantly between patients. Currently, there are limited guidelines on adjustment methods for its administration to individual needs. This study aimed to evaluate responsiveness of each patient to metyrapone and identify the patient characteristics associated with the indices of cortisol responsiveness following a low-dose metyrapone. This single-center retrospective observational study included 15 treatment-naïve patients, 7 of whom had Cushing’s disease and 8 had adrenal Cushing’s syndrome. Serum cortisol levels were measured hourly from the time of administration of 250 mg of metyrapone up to four hours afterward. Parameters analyzed included the nadir of serum cortisol levels (Fnadir), the difference between basal and nadir serum cortisol levels (ΔF), the time to nadir, and the characteristics of the patients. As a result, cortisol suppression curves showed significant variability among patients, particularly in the time to nadir. While the median time to nadir was 2 hours, 20% of patients required 4 hours or more, and these responses were not associated with patient characteristics. Fnadir was positively correlated with early-morning serum cortisol levels, serum cortisol levels after low-dose dexamethasone suppression test (LDDST), and urinary free cortisol (UFC) levels, whereas ΔF was positively correlated with late-night serum cortisol levels, serum cortisol levels after LDDST, and UFC levels. In conclusion, the duration of response to metyrapone appeared unpredictable in patients with Cushing’s syndrome and did not correlate with patient characteristics at baseline. Tracking the effect of metyrapone following a single low-dose administration may explain this variability and provide insights for optimizing individual dosing regimens. Further studies are required to validate these findings and guide more personalized treatment adjustments.